Horizontality, Negotiation, and Emergence: Toward a Philosophy of Environmental History - Cabral, Diogo de Carvalho (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2021)
In this article, I intend to creatively synthesize both the empirical findings and the theoretical formulations put forward by self-proclaimed environmental historians, as well as those by the scholars who preceded and influenced them. Establishing a dialogue with the broader field of Environmental Humanities, especially posthumanism, I propose three principles for writing environmental histories: horizontality, negotiation, and emergency. Horizontality refers to the inexistence of a given and absolute 'ground' for human life. We walk, build our houses, earn a living, and develop ideas and cultures, not on top of an ontological floor, but attending to and being attended by the bodies surrounding us, some of them animated and some not, some solid and some liquid and gaseous. To inhabit is to make oneself available to be inhabited. Mutual habitation weaves assemblages that are both the continent and the content of life. Negotiation alludes to the human conversation with a larger world, both animated and inanimate, about coexistence. Humans never get everything they want, just the way they want it, from their relationships with nonhumans. Though people rarely recognize this, the only way history can be made is through compromise with the rest of the biosphere. This means that humans are continuously becoming, as they and their activities couple themselves with other natural entities and their activities. Emergence, therefore, is the radical geo-historicity of all earthly things, whose character is never given beforehand but constituted as they make their way through the world.